1980
DOI: 10.1021/je60086a005
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and density of aqueous sodium carbonate and potassium carbonate solutions in the temperature range 20-90.degree.C and the pressure range 0-30 MPa

Abstract: The paper presents new experimental measurements of the viscosity of aqueous Na2C03 and K2C03 solutions In the temperature range 20-90 °C and the pressure range 0-30 MPa. The measurements cover the concentration range 0-1.7 m for the first salt and 0-2.5 m for the second and are believed to be accurate to ±1 %. The effect of pressure on the density of these solutions has also been measured. The paper contains correlations of the density and viscosity of Na2C03 and K2C03 In terms of temperature, pressure, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…A literature survey revealed that the number of measurements [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] reported for the density of Na 2 CO 3 (aq) cover very limited ranges of temperature (up to 383 K) and pressure (up to 30 MPa). Shilovskaya and Lenkova [30] measured the density of Na 2 CO 3 (aq) in the temperature range from 293 to 353 K and for concentrations between 0.1 and 0.4 mol l −1 .…”
Section: Experiments Density Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A literature survey revealed that the number of measurements [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] reported for the density of Na 2 CO 3 (aq) cover very limited ranges of temperature (up to 383 K) and pressure (up to 30 MPa). Shilovskaya and Lenkova [30] measured the density of Na 2 CO 3 (aq) in the temperature range from 293 to 353 K and for concentrations between 0.1 and 0.4 mol l −1 .…”
Section: Experiments Density Datamentioning
confidence: 99%
“…Postnikov [28] reported the densities of Na 2 CO 3 (aq) at saturation from 293 to 343 K. The uncertainty of the measurements is 0.01%. Only one dataset at high pressures reported by Correia and Kestin [40] for Na 2 CO 3 (aq) was found in the literature. In this work presented the measurements of density of aqueous Na 2 CO 3 solutions at temperatures between 293 and 363 K and at pressures up to 30 MPa for concentrations from 0 to 1.7 mol kg −1 .…”
Section: Experiments Density Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Gas viscosity was calculated using the method presented in Perry's Chemical Engineer's Handbook (Perry, 1984) and liquid viscosity was calculated using the correlation presented by Correia et al (1980).…”
Section: Methodsmentioning
confidence: 99%
“…Such a viscometer has been used by several researchers as an instrument for viscosity measurements (see, for example, DiPippo et al, 1966;Kestin et al, 1977Kestin et al, , 1978aKestin et al, ,b, 1980Correia et al, 1979;Correia and Kestin, 1980;Kestin and Shankland, 1981b, 1984band Krall et al, 1987, 1992. The theoretical and experimental problems of this technique have been discussed in detail elsewhere (Verschaffelt, 1915;Kestin et al, 1957aKestin et al, , 1958Kestin et al, , 1959Kestin et al, , 1981aNewell, 1959;Khalifa, 1976 andShankland, 1981b).…”
Section: Oscillating-disk Techniquementioning
confidence: 99%